PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ANDROID MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) - Eka Indriyani; Yeni Rahmawati ES.; Ira Vahlia (Universitas Muhammadiyah Metro, 2021)
This research and development aims to produce Android-based mathematics learning media using the Realistic Mathematics Education (RME) approach is valid and practical criteria. This development uses the ADDIE development model which consists of analyze, design, development, implementation, and evaluation. But due to time constraints and the Covid-19 pandemic, this research does not use the stage. implementation and only arrived at the development stage. The results of the analysis at the validation test stage by the validator produced a percentage based on 2 aspects, namely 80.67% material and 86% media aspects included, and The average percentage of learning media validity is 83.33% so that the learning media is included in the very valid category. Furthermore, the results of the analysis of the practicality test 10 phase by class X produced an average percentage of 86,66% and entered the very practical criteria. Based on the validity test and practicality test carried out, it can be concluded that the Android-based mathematics learning media uses the Realistic Mathematics Education (RME) approach declared valid and practical to use.